Effects of endocrine‐disrupting chemicals on hypothalamic oxytocin and vasopressin systems. Issue 1 (21st May 2021) - Reilly, Michael P.; Kunkel, M. Nicole; Thompson, Lindsay M.; Zentay, Andrew; Weeks, Connor D.; Crews, David; Cormack, Lawrence K.; Gore, Andrea C.
Abstract: Exposures to endocrine disrupting chemicals (EDCs) perturb hormonal systems. EDCs are particularly problematic when exposure happens in the fetus and infant due to the high sensitivity of developing organisms to hormone actions. Previous work has shown that prenatal polychlorinated biphenyl (PCB) exposure disrupts hypothalamic development, reproductive physiology, mate preference behavior, and social behaviors in a sexually dimorphic manner. Based on evidence that EDCs perturb social behaviors in rodents, we examined effects of PCBs on the neuropeptides oxytocin (OXT) and vasopressin (AVP) that are involved in regulating these behaviors. Rats were exposed prenatally (gestational days 16 and 18) to the weakly estrogenic PCB mixture Aroclor 1221 (0.5 or 1 mg/kg), to estradiol benzoate (EB, a positive control), or to the vehicle (3% dimethyl sulfoxide). In adult ( P90) brains, we counted immunolabeled oxytocin and vasopressin cell numbers in the paraventricular nucleus (PVN) and supraoptic nucleus (SON) of the hypothalamus. EDCs did not change absolute numbers of oxytocin or vasopressin cells in either region, although there were some modest shifts in the rostral‐caudal distribution. Second, expression of genes for these nonapeptides ( Oxt, Avp ), their receptors ( Oxtr, Avpr1a ), and the estrogen receptor beta ( Esr2 ), was determined by qPCR. In the PVN, there were dose‐dependent effects of PCBs in males ( Oxt, Oxtr ), and effects of EB in females ( Avp, Esr2 ). In the SON, Oxt, and Esr2 were affected by treatments in males. These changes to protein and gene expression caused by prenatal treatments suggest that transcriptional and posttranscriptional mechanisms play roles in mediating how EDCs reprogram hypothalamic development. Abstract : The distribution of oxytocin neurons in the PVN and SON was affected by prenatal PCB exposure. Shown is a series of immunolabeled sections from rostral (left) to caudal (right), relative to Bregma. Research Highlights: This study shows that a class of endocrine‐disrupting chemicals, PCBs, caused small but significant changes to the brain's vasopressin and oxytocin systems. Results suggest that transcriptional and/or posttranscriptional mechanisms play roles in how EDCs reprogram brain development.